JEP 2020
DOI: 10.7176/jep/11-12-02
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Opinions of the Usability of Simulations in a Mathematics Methods Course for Elementary Pre-Service Teachers

Abstract: The acceptance, implementation, and adoption of emerging technologies in teacher preparation programs has significantly evolved, and it is now seen as a tool that enhances teacher's teaching skills particularly during the first years of the program. The use of new technologies like Mixed-Reality Simulations (MRSs) in the preparation of future teachers, provides them the opportunity of developing teaching skills in a safe environment. In this article, the researchers studied the perceptions and opinions of Elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…These indicate that they generally (1) felt the simulated environment to be realistic; (2) felt enjoyment when using CartoonClass; and (3) thought that classroom simulations were helpful to their development of teaching competence (eg, noticing). Overall, these results are similar to those of previous research, in which the participants often reported positive perceptions of using virtual classroom environments (Aguilar & Telese, 2020; Dalinger et al, 2020; Spencer et al, 2019). In addition, the qualitative results also somewhat support the noticing improvement in the attending‐to skills as measured by the specific questions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These indicate that they generally (1) felt the simulated environment to be realistic; (2) felt enjoyment when using CartoonClass; and (3) thought that classroom simulations were helpful to their development of teaching competence (eg, noticing). Overall, these results are similar to those of previous research, in which the participants often reported positive perceptions of using virtual classroom environments (Aguilar & Telese, 2020; Dalinger et al, 2020; Spencer et al, 2019). In addition, the qualitative results also somewhat support the noticing improvement in the attending‐to skills as measured by the specific questions.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, various studies have looked at users' perceptions of digital classroom simulations, with many reporting that such simulations were viewed as authentic, immersive, and/or confidence‐boosting (Aguilar & Telese, 2020; Dalinger et al, 2020; Spencer et al, 2019). For example, Aguilar and Telese studied 166 pre‐service elementary mathematics teachers' perceptions of their experience during three 7–12 minute mixed‐reality virtual simulations within a mathematics methods course.…”
Section: Literature Reviewmentioning
confidence: 99%